A novel defined TLR3 agonist as an effective vaccine adjuvant - Ko, Kwang Hyun; Cha, Seung Bin; Lee, Seung-Hwan; Bae, Hyun Shik; Ham, Chul Soo; Lee, Min-Gyu; Kim, Dong-Ho; Han, Seung Hyun (Frontiers in Immunology, 2023)
Synthetic double-stranded RNA analogs recognized by Toll-like receptor 3 (TLR3) are an attractive adjuvant candidate for vaccines, especially against intracellular pathogens or tumors, because of their ability to enhance T cell and antibody responses. Although poly(I:C) is a representative dsRNA with potent adjuvanticity, its clinical application has been limited due to heterogeneous molecular size, inconsistent activity, poor stability, and toxicity. To overcome these limitations, we developed a novel dsRNA-based TLR3 agonist named NexaVant (NVT) by using PCR-coupled bidirectional in vitro transcription. Agarose gel electrophoresis and reverse phase-HPLC analysis demonstrated that NVT is a single 275-kDa homogeneous molecule. NVT appears to be stable since its appearance, concentration, and molecular size were unaffected under 6 months of accelerated storage conditions. Moreover, preclinical evaluation of toxicity under good laboratory practices showed that NVT is a safe substance without any signs of serious toxicity. NVT stimulated TLR3 and increased the expression of viral nucleic acid sensors TLR3, MDA-5, and RIG-1. When intramuscularly injected into C57BL/6 mice, ovalbumin (OVA) plus NVT highly increased the migration of dendritic cells (DCs), macrophages, and neutrophils into inguinal lymph node (iLN) compared with OVA alone. In addition, NVT substantially induced the phenotypic markers of DC maturation and activation including MHC-II, CD40, CD80, and CD86 together with IFN- production. Furthermore, NVT exhibited an appropriate adjuvanticity because it elevated OVA-specific IgG, in particular, higher levels of IgG2c (Th1-type) but lower IgG1 (Th2-type). Concomitantly, NVT increased the levels of Th1-type T cells such as IFN-+CD4+ and IFN-+CD8+ cells in response to OVA stimulation. Collectively, we suggest that NVT with appropriate safety and effectiveness is a novel and promising adjuvant for vaccines, especially those requiring T cell mediated immunity such as viral and cancer vaccines.